2001
DOI: 10.1002/1521-4095(200108)13:15<1167::aid-adma1167>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fabrication of Polyelectrolyte Multilayer Thin Films Using Spin-Assembly

Abstract: Spin‐assembly is an excellent method for controlling the amount and thickness of adsorbed polyelectrolyte in fabricating multilayer thin films. These films are investigated by means of ellipsometry and UV‐vis spectroscopy and their spectral properties are used to determine the effect of the polyelectrolyte concentration, the speed of rotation, and other experimental parameters on the film thickness and uniformity. Adjusting these parameters allows fine‐tuning of the multilayer thin films and provides the spin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
194
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(206 citation statements)
references
References 3 publications
8
194
0
4
Order By: Relevance
“…A further possibility for preparing composite films is the spin self-assembly method. 14,15 In contrast to those mentioned above, this method allows the rapid production of films with controlled layered structure and extremely low surface roughness on planar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A further possibility for preparing composite films is the spin self-assembly method. 14,15 In contrast to those mentioned above, this method allows the rapid production of films with controlled layered structure and extremely low surface roughness on planar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a spin coater is operated in a conventional manner with excess solution (polycation or polyanion) applied to a substrate before spinning, during which time solution is first rapidly (Ͻ1 s) expelled from the surface, following which a thin film of polyelectrolyte solution more slowly thins and dries over the course of 2-10 s. To build up polyelectrolyte multilayers in an LbL fashion, this spin-coating step is applied sequentially to solutions of oppositely charged polyelectrolytes with intervening rinsing steps also achieved using the spin coater. It was shown recently [11][12][13] that such a method, here termed polyelectrolyte spin assembly (PSA), allows for rapid processing and for uniform coating of the substrate. Furthermore, the process is found to produce highly ordered coatings that are smoother and thicker when compared with the coatings attained by dipping technique applied to identical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportionality constant-or slope of thickness versus cycle number-was larger for PSA than for the dipping deposition process. 13 The effect of spinning rate on the layer thickness increment for PSA of salt-free solutions was studied by Chiarelli et al, 12 who found using ellipsometry that increasing the spin speed leads to thinner, perhaps more compacted, multilayers with an asymptotic behavior at high spin speeds. The observation was explained by the "increased mechanical forces" experienced by the films at higher spin-ning rates that lead to a shorter contact time between polyelectrolyte solution and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one can control thickness (Lo¨sche et al, 1998;Dubas and Schlenoff, 1999), permeability (Rmaile and Schlenoff, 2003), morphology (Antipov et al, 2003;McAloney et al, 2003;Mendelsohn et al, 2000), and density (Dragan et al, 2003). Recently the technique has been modified to assemble the alternate layers using a spin-coater, which reduces the assembly times and adsorption solution volumes considerably (Chiarelli et al, 2001;Cho et al, 2001;Lee et al, 2003Lee et al, , 2001.…”
Section: Polyelectrolyte Multilayersmentioning
confidence: 99%